2006
DOI: 10.1063/1.2200737
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and energy transfer processes in (Tm3+, Nd3+) doped tungstate fluorophosphate glass

Abstract: We investigate the linear optical properties and energy transfer processes in tungstate fluorophosphate glass doped with thulium ͑Tm 3+ ͒ and neodymium ͑Nd 3+ ͒ ions. The linear absorption spectra from 370 to 3000 nm were obtained. Transitions probabilities, radiative lifetimes, and transition branching ratios were determined using the Judd-Ofelt ͓Phys. Rev. 127, 750 ͑1962͒; J. Chem. Phys. 37, 511 ͑1962͔͒ theory. Frequency up-conversion to the blue region and fluorescence in the infrared were observed upon pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The JO parameters obtained in the present work indicated the trend as Ω 2 > Ω 4 > Ω 6 as the same trend has been found in previous reports (Chung and Heo, 2001); (Martinez et al, 1998); (Thomas et al, 1992); (Walsh and Barnes, 2004). Nevertheless, the trend of the Tm 3+ /Nd 3+ codoped glass (Brandão et al, 2006) showed higher Ω 6 than Ω 4 (Ω 2 > Ω 6 > Ω 4 ). Since the intensity parameter ( 2 ) is related to the degree of covalence (Digonnet, 1993), the large value of  2 in the present work indicates the presence of covalent bonding between Tm 3+ and Nd 3+ .…”
Section: Jo Parametersmentioning
confidence: 91%
See 3 more Smart Citations
“…The JO parameters obtained in the present work indicated the trend as Ω 2 > Ω 4 > Ω 6 as the same trend has been found in previous reports (Chung and Heo, 2001); (Martinez et al, 1998); (Thomas et al, 1992); (Walsh and Barnes, 2004). Nevertheless, the trend of the Tm 3+ /Nd 3+ codoped glass (Brandão et al, 2006) showed higher Ω 6 than Ω 4 (Ω 2 > Ω 6 > Ω 4 ). Since the intensity parameter ( 2 ) is related to the degree of covalence (Digonnet, 1993), the large value of  2 in the present work indicates the presence of covalent bonding between Tm 3+ and Nd 3+ .…”
Section: Jo Parametersmentioning
confidence: 91%
“…The values of the JO parameters were, respectively, 8.1610 -24 , 3.2010 -24 and 2.6710 -24 m 2 for  2 ,  4 and  6 . The JO intensity parameters of the present work compared with the results of the Tm 3+ /Nd 3+ codoped glasses (Brandão et al, 2006); (Chung and Heo, 2001), the Tm doped fibers (Peterka et al, 2004); (Walsh and Barnes, 2004), and the Nd doped fiber preform and glass (Martinez et al, 1998); (Thomas et al, 1992) are listed in Table 2.…”
Section: Jo Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…Os materiais dopados com Tm 3+ têm atraído grande interesse dos pesquisadores devido as suas aplicações em dispositivos como laser de estado sólido, LEDs, displays e dispositivos de armazenamento de dados [4,[8][9][10][11][12], devido à sua intensa emissão de luz azul, em torno de 480 nm, quando utilizado em sistemas que envolvem codopagem com Yb 3+ , além da área médica que utiliza a região do infravermelho [13]. Os vidros de germanato dopados com vários íons de terras-raras • Aumento no índice de refração linear e não-linear do vidro;…”
Section: Lista De Ilustraçõesunclassified